2015
DOI: 10.1007/s13593-014-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Ecological principles underlying the increase of productivity achieved by cereal-grain legume intercrops in organic farming. A review

Abstract: World population is projected to reach over nine billion by the year 2050, and ensuring food security while mitigating environmental impacts represents a major agricultural challenge. Thus, higher productivity must be reached through sustainable production by taking into account climate change, resources rarefaction like phosphorus and water, and losses of fertile lands. Enhancing crop diversity is increasingly recognized as a crucial lever for sustainable agro-ecological development. Growing legumes, a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
460
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(551 citation statements)
references
References 132 publications
18
460
4
8
Order By: Relevance
“…Introducing flower resources in these grass strips may also allow supporting flower visitors. Intercropping that provides benefits towards pest control can also lead to an increase of nitrogen and carbon in soils when leguminous plants are combined with cereals, potentially favouring soil fertility and reducing nutrient run-off with fewer fertilizer applications (Bedoussac et al, 2015;Cong et al, 2014). As for agroforestry systems, a recent meta-analysis shows that the introduction of trees generally reduces soil erosion, increases soil fertility and nutrient cycling as well as biodiversity (but the type of biodiversity, hence the functions it can exert, was not specified) (Torralba et al, 2016).…”
Section: Soil Erosion and Nutrient Run-offmentioning
confidence: 99%
“…Introducing flower resources in these grass strips may also allow supporting flower visitors. Intercropping that provides benefits towards pest control can also lead to an increase of nitrogen and carbon in soils when leguminous plants are combined with cereals, potentially favouring soil fertility and reducing nutrient run-off with fewer fertilizer applications (Bedoussac et al, 2015;Cong et al, 2014). As for agroforestry systems, a recent meta-analysis shows that the introduction of trees generally reduces soil erosion, increases soil fertility and nutrient cycling as well as biodiversity (but the type of biodiversity, hence the functions it can exert, was not specified) (Torralba et al, 2016).…”
Section: Soil Erosion and Nutrient Run-offmentioning
confidence: 99%
“…This statement was also mirrored in the agricultural utilised area of the two groups: farms which cultivated grain legumes had on average more agricultural utilised area (93.1 ha) and more farmland (48.9 ha) than those which did not cultivate grain legumes (88.6 ha utilised agricultural area, 41.8 ha farmland). However, grain legumes can be successfully used in rotation and intercropping systems (Bedoussac et al 2015) and can therefore also be incorporated in crop rotations on farms with less arable land. Here, the lack of knowledge on grain legume cultivation affects again the decision-making process.…”
Section: Experience Of Farmers Who Do Not Cultivate Grain Legumesmentioning
confidence: 99%
“…Due to their ability to fix nitrogen from the air symbiotically with rhizobia species, legumes are very important in agriculture, especially in organic production (Bedoussac et al 2015). Legumes supply atmospheric N 2 to subsequent crops when grown in rotation and incorporated into the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intercropping allows the increase of natural resources use efficiency by positive interspecific interactions (e.g. Bedoussac et al, 2015). Many studies on grain legume-cereal intercrops have shown advantages over the sole crops in low input systems such as the increase of the overall yield (sum of the species) and the grain protein concentration improvement of the cereal (e.g.…”
Section: Topical Issuementioning
confidence: 99%
“…Many studies on grain legume-cereal intercrops have shown advantages over the sole crops in low input systems such as the increase of the overall yield (sum of the species) and the grain protein concentration improvement of the cereal (e.g. Bedoussac et al, 2015). In addition, intercropping warm-season crops constitutes a feasible alternative to promote hetero-geneity within-fields and therefore sustain biodiversity (weeds, B A Fig.…”
Section: Topical Issuementioning
confidence: 99%